(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2025)
This article addresses issues related to increasing the role of the state in coordinating the investment climate, ensuring the participation of the state in improving the attractiveness of the investment climate, and correctly defining the strategies that the state must adopt to ensure the attractiveness of the investment climate.